Performance in association of cultivars of cassava (Manihot esculenta Cranz) and cowpea (Vigna unguiculata Walp.) of different growth habits - Rodríguez Montero, Werner (1984)
The association of cowpeas and cassava appears to offer a means of exploiting to the fullest most resources of the humid tropical environment, both species are relatively tolerant to adverse soil conditions. The combination of a tall long-season crop (cassava) with a shorter, quicker growing (cowpea) should be the ideal combination (Sánchez, 1976) for exploiting the light resources of such an environment as well as minimizing interspecific competition. The objective of the present study was to determine if cassava and cowpea cultivars of different growth habits interacted differently when grown in association. It was hoped a combination of cassava and cowpea plant type could be found which maximized the resources available.